EVALUATING POST-DIVORCE WOMEN'S AND CHILDREN'S RIGHTS FUNDING APPLICATION USING OWASP TOP TEN AND ISO 25010:2023 - Oktariani, Deta; Utami, Ema (JIKO (Jurnal Informatika dan Komputer), 2025)
Evaluating an information system from both performance and security aspects is crucial for anticipating and improving the quality of the information system. A High Religious Court in collaboration with the Provincial Government developed a web-based application to support one of its services, to monitor court decisions regarding alimony payments from former husbands to former wives and children in divorce cases involving civil servants. This is certainly very important because before the existence of this application, there were many complaints filed due to the non-payment of alimony. To ensure that the application runs in accordance with its purpose and that the data is secure, a comprehensive system evaluation is required. The main objective of this evaluation is to identify vulnerabilities and their mitigations, as well as to ensure that the functions in the application work as expected, so that the application's goals are achieved. To achieve this goal, this study uses the ISO 25010:2023 information system standard integrated with OWASP Top Ten to evaluate its security This study uses five ISO 25010:2023 characteristics selected according to the system's goals. The results show that the combination of ISO 25010:2023 and OWASP Top Ten effectively identifies vulnerabilities in the application's functions and security comprehensively. Overall, the functions in the application have run as expected, although there are still several things that need to be improved to enhance the quality and secure its data.